Pengaruh Independensi, Kompetensi dan Pengalaman Kerja Auditor Terhadap Kualitas Audit - Maria Immaculata Adisti; J Sabas Setyohadi (Sosio e-Kons, 2019)
The quality audit is conducted by an independent and competent auditor. This research is aimed at describing the influence auditor’s independence, competence and working experience upon audit quality in the Office of Public Accountant in Jakarta. The method employed in this research surveys with the technique being questionnaire. The population for this research is all auditors working in the Office of Public Accountant in Jakarta. The technique used to make sampling in this research is nonrandom sampling/nonprobability sampling with 180 samples. The data is analyzed by using the Multiple Regression Model. The result of research indicates that auditor’s independence, competence, and working experience have a positive and significant impact on audit quality. In addition, the result shows that there is a low average (mean) of the correlation between independence, competence, and working experience and audit quality in a partial way.